2019
DOI: 10.3390/polym11050765
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thermo-Responsive Block-Graft Copolymer Based on PCL and PEG Analogs, and Preparation of Hydrogel via Click Chemistry

Abstract: Thermo-responsive cross-linkable mPEG-b-[PCL-g-(MEO2MA-co-OEGMA)]-b-mPEG was synthesized by ring-opening polymerization (ROP) and atom transfer radical polymerization (ATRP). Then, the cross-linkable block-graft copolymer was used to prepare hydrogel via a copper-catalyzed 1,3-dipolar azide-alkyne cycloaddition reaction. The chemical structure and composition of copolymer were characterized by proton nuclear magnetic resonance (1H NMR), Fourier-transform infrared (FT-IR) and gel permeation chromatography (GPC)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…The gel has a tendency to shrink and lose water at 40 °C, which proves that the gel has temperature sensitivity. This is because, when the temperature rises to 40 °C, the hydrogen bond breaks, and the temperature-sensitive polymer chain P(MEO 2 MA- co -OEGMA) chain begins to shrink [ 39 ] by squeezing water out of the gel. Thus, this shows a state of de-swelling.…”
Section: Resultsmentioning
confidence: 99%
“…The gel has a tendency to shrink and lose water at 40 °C, which proves that the gel has temperature sensitivity. This is because, when the temperature rises to 40 °C, the hydrogen bond breaks, and the temperature-sensitive polymer chain P(MEO 2 MA- co -OEGMA) chain begins to shrink [ 39 ] by squeezing water out of the gel. Thus, this shows a state of de-swelling.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that due to the hydrogen bonds formed between water molecules and the oligo (ethylene glycol) graft chain that is hydrophilic, the synthesized copolymer showed better solubility in water and formed a clear solution, compared to just PEG-PCL-PEG, which displayed a cloudy solution in water. In addition, the improvement in the thermo-responsiveness of the copolymer was attributed to the OEGMA and MEO2MA molecules, and the formulation showed a gelation temperature of 30 • C (Shang et al, 2019).…”
Section: Pcl-peg Based Thermogelsmentioning
confidence: 99%
“…The solubility and temperature responsiveness of PEG-PCL based thermogels was improved via the synthesis of a mPEG-b-[PCL-g-(MEO2MA-co-OEGMA)]-b-mPEG blockgraft copolymer by Shang et al (2019). Results showed that due to the hydrogen bonds formed between water molecules and the oligo (ethylene glycol) graft chain that is hydrophilic, the synthesized copolymer showed better solubility in water and formed a clear solution, compared to just PEG-PCL-PEG, which displayed a cloudy solution in water.…”
Section: Pcl-peg Based Thermogelsmentioning
confidence: 99%
“…A 3D and interconnected structure, similar to that of the extracellular matrix, was obtained through the hybridization of PEG-PCL with PNIPAAm, resulting in a penta-block PNIPAAm-PCL-PEG-PCL-PNIPAAm TSH for application in wound healing. [70] Such formulation displayed excellent biocompatibility and was able to gel at 37 °C, its pore size being ideal for fibroblast attachment as well as for the improvement of cell adhesion and proliferation. [70] The focus of this review is driven by PNIPAAm hydrogel and its derivatives.…”
Section: Pcl-peg-based Thermosensitive Hydrogelsmentioning
confidence: 99%
“…[70] Such formulation displayed excellent biocompatibility and was able to gel at 37 °C, its pore size being ideal for fibroblast attachment as well as for the improvement of cell adhesion and proliferation. [70] The focus of this review is driven by PNIPAAm hydrogel and its derivatives. Therefore, a detailed description of its chemical structure and relationship with the LCST transition, synthesis, and main properties are provided in the following sections.…”
Section: Pcl-peg-based Thermosensitive Hydrogelsmentioning
confidence: 99%